Parameter study of hopping mechanism for one legged crank-type hopping robot - Mohd Zakaria, Muhammad Akmal (2015)
Micro-machining is expected to play an important role in today's manufacturing technology. However, the traditional down-scaling process creates challenges relating to process stability and materials behaviour especially for small difficult-to-machine made materials. Therefore, a suitable material removal process to perform micro-machining on cylindrical components is spark erosion process. In this study, the new hybrid micro-machining process is developed. This process is synonym with the name of wire electrical discharged turning (WEDT) which incorporates a turning process of rotating workpiece to continuous travelling electrode wire in electrical discharged conditions produced by wire electrical discharge machine. The objective of this research is to develop and evaluate the advance machinery and equipment for rotary axis mechanism that is being used to rotate the workpieces. The research focuses on optimizing the process parameter of hybrid WEDT for micro-machining straight shaft cylindrical component made of Ti6Al4V as materials. The issues pertaining to hybrid WEDT process on surface roughness (Ra) in the past have been explored comprehensively. The rotary axis mechanism that works well with WEDM machine has been successfully developed and the micro turning operations has been performed. The parameter optimization consideration on Ra begins with two stage screening. Firstly, the suitable combination parameter and its range is properly selected. Then, the selection of appropriate parameters and range is further screened by Taguchi orthogonal array L12. From the 11 process parameters that consist of electrical, non-electrical and rotary axis mechanism characteristics, only four has been selected to perform optimization by response surface methodology (RSM) which are intensity of pulse, voltage open, wire tension and rotational spindle speed. The other parameters are fixed at best level to produce low Ra value which is identified by Alicona Infinite Focus microscope (IFM). The optimal Ra that is produced by experiment through desirability approach is as much as 4.0143 μm with relative error as much as 5.9% compared to the prediction. The parameter and its level are pulse intensity of 8 Notch, wire tension of 14.8 Newton, voltage of 7 Notch and rotational spindle speed of 2390 rev/min. The machined parts surface is being deteriorated accordingly to the violent energy density generated by high pulse intensity and voltage, low wire tension and spindle speed.